2000
DOI: 10.1104/pp.124.2.751
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Brassinosteroid Insensitive 1 Receptor-Like Kinase Autophosphorylates on Serine and Threonine Residues and Phosphorylates a Conserved Peptide Motif in Vitro

Abstract: BRASSINOSTEROID-INSENSITIVE 1 (BRI1) encodes a putative Leucine-rich repeat receptor kinase in Arabidopsis that has been shown by genetic and molecular analysis to be a critical component of brassinosteroid signal transduction. In this study we examined some of the biochemical properties of the BRI1 kinase domain (BRI1-KD) in vitro, which might be important predictors of in vivo function. Recombinant BRI1-KD autophosphorylated on serine (Ser) and threonine (Thr) residues with p-Ser predominating. Matrix-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
219
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(227 citation statements)
references
References 53 publications
7
219
0
1
Order By: Relevance
“…As previously reported (15), BAK1 can bind to and transphosphorylate BRI1 in vivo, and this is thought to be essential to enhance signaling output in planta. Importantly, both components of this functional interaction can be examined in vitro by monitoring the ability of BAK1 to (i) bind to BRI1 and (ii) increase the transphosphorylation activity of BRI1 using the BR13 synthetic peptide as substrate (15,25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported (15), BAK1 can bind to and transphosphorylate BRI1 in vivo, and this is thought to be essential to enhance signaling output in planta. Importantly, both components of this functional interaction can be examined in vitro by monitoring the ability of BAK1 to (i) bind to BRI1 and (ii) increase the transphosphorylation activity of BRI1 using the BR13 synthetic peptide as substrate (15,25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). The important conclusion is that BAK1 Tyr-610 phosphorylation is required to fully activate BRI1, which is recognized to be one of the important factors that influences signaling leading to plant growth (1,15,25,26). To further explore the molecular basis for the dwarf phenotype of the Y610F transgenic plants, we used ATH1 GeneChips (Affymetrix) to monitor relative transcript levels in plants expressing native sequence BAK1-Flag or BAK1(Y610F)-Flag in the bak1-4 bkk1-1 double mutant background.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide, dubbed CLV1 pT868, comprises residues 863-875 of the Arabidopsis CLAVATA1 receptor-like kinase (RLK): PEYAY(pT)LKVDEKS. Multiple sequence alignment of kinase domains of RLKs indicates that the threonine that we phosphorylated in this CLV1 pT868 peptide corresponds to Ser1060 of the BRI1 RLK, one of two neighboring residues phosphorylated at the C-terminal end of the activation loop of kinases (66). This suggests pT868 of CLV1 might also be phosphorylated in vivo, making it the most likely of our KI-FHA-binding phosphopeptide candidates to be physiologically relevant.…”
Section: Residual Dipolar Coupling Analysismentioning
confidence: 80%
“…Many phosphorylation sites of BRI1 have recently been identified by mass spectrometry analysis of recombinant BRI1 expressed in E. coli or BRI1 immunoprecipitated from plant extracts [21,22]. Mutation studies of the phosphorylation residues demonstrated that some of the phosphorylation events increase and some reduce the BRI1 activity, as measured by the ability of the mutated BRI1 protein to phosphorylate a synthetic substrate and to rescue a bri1 mutant [21].…”
Section: Br Activation Of Bri1 and Bak1 Receptor Kinasesmentioning
confidence: 99%